Characterizing a Culture of Training and Safety: A Qualitative Case Study in Radiation Oncology. - Garza Lozano, Ronnie (Radiation Therapist)
Background This qualitative case study was conducted in response to the growing body of literature focused on specific recommendations, factors, and barriers that influence a culture of safety. Based on recent reports, the most critical safety issues are failure to communicate and failure to acknowledge others as professionals across departmental boundaries. Purpose To explore how one radiation oncology organization's infrastructure, information and communication patterns, and values and philosophy of care contributed to the creation of a culture of effective training strategies that resulted in comprehensive patient safety. Methods Information was gathered through semistructured one-on-one interviews with various members of the radiation oncology team. In this article, the participants' names are pseudonyms. Results The organization created a culture in which the staff shares a sense of ownership for the clinical facilities, and the administration makes the "softer" aspects of care - knowing the patient personally - a top priority. Conclusion This organization's enhanced communication and knowledge-sharing practices improve patient safety and should serve as a model for others.